(untitled) (Eurasian Journal of Engineering and Technology, 2026)
The article discusses the need to create equipment for determining the multi-cycle tensile deformation of knitted fabrics and the possibility of a more complete analysis of the dimensional stability of knitted fabrics by determining it, as well as the creation of a special pulsation device for this purpose. The composition of the main parts of the pulsator device and its use, as well as a schematic and external drawing of the device, are given.